Baricitinib in pediatric chronic immune thrombocytopenia and associated autoimmune conditions: a case report - López de Hontanar Torres, G.; Zubicaray, J.; Sebastián, E.; Hernández-Martín, A.; Iriondo, J.; Sevilla, J. (Frontiers in Pediatrics, 2024)
Immune thrombocytopenia (ITP) is a disease characterized by platelet destruction, presenting substantial challenges in clinical practice. The classic first line therapeutic management includes corticosteroids and intravenous immunoglobulins. Although it is less frequent in children than in adults, there is a significant percentage of patients, up to 47% according to the Pediatric and Adult Registry on Chronic ITP, who require second-line or further treatment, due to non-response to the first line treatment or persistence of disease, among other reasons. Several second line approaches for its treatment are currently in use, including increasing platelet production with thrombopoietin receptor agonists. We report the case of a 16-year-old patient with ITP and alopecia areata successfully treated with baricitinib, a reversible and selective JAK 1/2 inhibitor. Baricitinib is currently in use for the treatment of several autoimmune conditions and has been shown to increase platelet counts in these patients. This phenomenon has been linked to increased TPO signaling and reduced platelet destruction. There are promising preliminary results of adult ITP patients treated with baricitinib. This case report is the first reported use of baricitinib in ITP in the pediatric and adolescent setting, potentially leading to its use in this condition.